Novel GNAL mutation with intra-familial clinical heterogeneity: Expanding the phenotype. (February 2016) - Carecchio, Miryam; Panteghini, Celeste; Reale, Chiara; Barzaghi, Chiara; Monti, Valentina; Romito, Luigi; Sasanelli, Francesco; Garavaglia, Barbara
Abstract: Introduction: Mutations in GNAL have been associated with adult-onset cranio-cervical dystonia, but a limited number of cases have been reported so far and the clinical spectrum associated with this gene still needs to be fully characterized. Methods: We identified an Italian family with adult-onset, dominantly-inherited dystonia whose members presented with different combinations of dystonia affecting the cervical, oro-mandibular and laryngeal regions associated with prominent tremor in some cases. Pure asymmetric upper limb dystonic tremor was present in one of the members and jerky cervical dystonia was also observed. A dedicate dystonia gene panel (Illumina) was used to screen for dystonia-associated genes and Sanger sequencing was performed to confirm results obtained and to perform segregation analysis. Results: A novel single-base mutation in GNAL exon 9 (c.628G>A; p.Asp210Asn) leading to an aminoacidic substitution was identified and confirmed by Sanger sequencing. In silico prediction programmes as well as segregation analysis confirmed its pathogenicity. Clinically, no generalization of dystonia was observed after onset and DBS lead to an excellent motor outcome in two cases. Conclusion: We report a novel GNAL mutation and expand the clinical spectrum associated with mutations in this gene to comprise pure asymmetric dystonic tremor and a jerky cervical phenotype partially mimicking DYT11 positive cases. Highlights: GNAL mutations have been associated with adult-onset cranio-cervical dystonia. We report a novel missense GNAL mutation in a family with phenotypic heterogeneity. We expand GNAL-associated phenotype to comprise pure upper limb dystonic tremor and prominent tremulous and jerky dystonia. An excellent motor outcome was demonstrated in two affected subjects following bilateral GPi DBS.